BIOCHEMICAL PARAMETERS OF RAT’S BLOOD UNDER THE CHRONIC OPIOID EXPOSURE - Vilkhova, I.V.; Mateshuk-Vatseba, L.R.; Logash, M.V.; Kantser, O.V. (World of Medicine and Biology, 2021)
The purpose of the study was to establish changes in some biochemical parameters of rat's blood, which indicate the functional state of the kidney with prolonged administration of nalbuphine in the experiment. As a result of the study, it was found that the administration of small doses of nalbuphine during a 12-week experiment leads to impaired renal filtration function, which was first detected after 4 weeks of nalbuphine administration, reaches its maximum manifestation after 8 weeks of nalbuphine administration and stabilizes in the following terms, as evidenced by the dynamics of creatinine and urea in the serum of rats. Impaired renal reabsorption function was first detected after 2 weeks of nalbuphine administration and acquires a pronounced manifestation after 8, 10 and 12 weeks of the experiment, as evidenced by the dynamics of calcium and phosphorus in the rats' serum.
Keywords: kidney; urea; creatinine; phosphorus; calcium; serum; nalbuphine; rat